2022
DOI: 10.1111/irj.12375
|View full text |Cite
|
Sign up to set email alerts
|

What can analysis of 47 million job advertisements tell us about how opportunities for homeworking are evolving in the United Kingdom?

Abstract: Using an extensive database of job adverts, we investigate the extent to which homeworking is likely to continue. We track how advertisement language has evolved to indicate homeworking opportunities and how the characteristics of jobs offering these opportunities have changed, including a greater degree of polarisation in opportunity by salary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In addition, we find that the increased prevalence of remote working is associated with increased job security. This reflects other evidence which demonstrates that employers are increasingly offering jobs on a remote working basis to attract and retain workers (Darby et al, 2022; Felstead, 2022, p. 105).…”
Section: Discussionsupporting
confidence: 70%
“…In addition, we find that the increased prevalence of remote working is associated with increased job security. This reflects other evidence which demonstrates that employers are increasingly offering jobs on a remote working basis to attract and retain workers (Darby et al, 2022; Felstead, 2022, p. 105).…”
Section: Discussionsupporting
confidence: 70%
“…The impact of the pandemic on patterns of work also varied significantly across and within nations. For example, while up to 50% of workers in the United States and Europe worked from home or other remote locations at the peak of the 2020 lockdowns (Darby et al, 2022), not everyone had this opportunity, and not all countries were subject to lockdowns and associated social distancing rules (Dobbins, 2021; Kulik, 2022). Indeed, right‐wing populist governments in countries like Brazil and Indonesia were complacent and slow in reacting to COVID‐19 (Lassa & Booth, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that commuting is often an unviable option for women because of care responsibilities and they may self-impose tight geographical limits to ‘their’ labour markets (Wheatley, 2017; Williams et al, 2008). The suggestion is that with the UK labour market offering more homeworking opportunities for knowledge workers (Darby et al, 2022) we may expect an incremental erosion of the employment inequalities associated with commuting (Chung et al, 2021). As Saia et al (2022: 7) have argued in relation to new homeworking opportunities for people with disabilities, the pandemic, as a point of discontinuity, may serve the broader equal opportunities agenda: ‘The pendulum has swung, but we need to make sure it never becomes still.’ However, if organisations embrace telecommuting because it may offer advantages from work extensification, this may disproportionately disadvantage women for similar reasons that make long-distance commuting unviable for many (Nemoto, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As Saia et al (2022: 7) have argued in relation to new homeworking opportunities for people with disabilities, the pandemic, as a point of discontinuity, may serve the broader equal opportunities agenda: ‘The pendulum has swung, but we need to make sure it never becomes still.’ However, if organisations embrace telecommuting because it may offer advantages from work extensification, this may disproportionately disadvantage women for similar reasons that make long-distance commuting unviable for many (Nemoto, 2013). So, as telecommuting becomes more prevalent, social policymakers and employers need to deeply consider how it impacts on their equality and diversity agenda (Darby et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation